INTERDISCIPLINARY RELATIONSHIPS BETWEEN SOCIAL WORKERS AND OTHER PROFESSIONS IN HANDLING CHILDREN WITH SPECIAL NEEDS AT SURYAKANTI HEALTH CLINIC BANDUNG, INDONESIA - Ocktilia, Helly; Wigaringtyas, Odha; Tukino, Tukino; Nainggolan, Atirista (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2018)
Interdisciplinary relations of social workers seen through interpersonal relationships of social workers with other professions, organization setting of interdisciplinary work systems and the funding model allocated for such interdisciplinary work. The researchers were interested in seeing the implementation of these three aspects with the aim of knowing the description of social worker relations with other professions in Suryakanti Health Clinic Bandung, Indonesia. The method used in this research was a qualitative descriptive method with ten informants consisting of two social workers, one doctor, one psychologist, four therapists, one nurse and one employee of management. Data collection techniques used interviews, observations, field notes, and document usage. Data validity was performed using credibility test with increasing perseverance, reference adequacy as well as triangulation of technique and time. The results showed that the clinic policy of separating the interdisciplinary works into inter-professional and referral divisions has brought about social workers lose their role as mediator and no longer participate in recommendation formulation with an interdisciplinary team. Consequently, all the activities related to the patient handling were mostly based on a good interpersonal relationship between the social workers and other professions. Similarly, due to the limited funding, the clinic provided the social workers with only transportation expenses, while the service fees expected to come from the parent of the visited patient were not always obtained.